MENGENAL KEPITING Ashtoret lunaris (FORSKAL, 1775) DARI SUKU MATUTIDAE (CRUSTACEA: DECAPODA: BRACHYURA) - Ernawati Widyastuti (Pusat Penelitian Oseanografi LIPI, 2018)
KNOWING Ashtoret lunaris (FORSKAL, 1775) FROM MATUTIDAE (CRUSTACEA: DECAPODA: BRACHYURA). Ashtoret lunaris is a species of genus Ashtoret from Matutidae. This crab is known as “yellow moon crab”, because it has a yellow and rounded carapace like a full moon. These crabs are nocturnal and live in coastal areas with soft substrate. The crab has a wide distribution spanning from the Red Sea to South Africa, Asia and Australia. Some biological aspects such as morphology, systematic, habitat, feeding habit, distribution and others are discussed in this paper.